Long term tapering versus standard prednisolone treatment for first episode of childhood nephrotic syndrome: phase III randomised controlled trial and economic evaluation. (23rd May 2019) - Webb, Nicholas J A; Woolley, Rebecca L; Lambe, Tosin; Frew, Emma; Brettell, Elizabeth A; Barsoum, Emma N; Trompeter, Richard S; Cummins, Carole; Deeks, Jonathan J; Wheatley, Keith; Ives, Natalie J
Abstract: Objective: To determine whether extending initial prednisolone treatment from eight to 16 weeks in children with idiopathic steroid sensitive nephrotic syndrome improves the pattern of disease relapse. Design: Double blind, parallel group, phase III randomised placebo controlled trial, including a cost effectiveness analysis. Setting: 125 UK National Health Service district general hospitals and tertiary paediatric nephrology centres. Participants: 237 children aged 1-14 years with a first episode of steroid sensitive nephrotic syndrome. Interventions: Children were randomised to receive an extended 16 week course of prednisolone (total dose 3150 mg/m 2 ) or a standard eight week course of prednisolone (total dose 2240 mg/m 2 ). The drug was supplied as 5 mg tablets alongside matching placebo so that participants in both groups received the same number of tablets at any time point in the study. A minimisation algorithm ensured balanced treatment allocation by ethnicity (South Asian, white, or other) and age (5 years or less, 6 years or more). Main outcome measures: The primary outcome measure was time to first relapse over a minimum follow-up of 24 months. Secondary outcome measures were relapse rate, incidence of frequently relapsing nephrotic syndrome and steroid dependent nephrotic syndrome, use of alternative immunosuppressive treatment, rates of adverse events, behavioural change using the Achenbach child behaviour checklist, quality adjusted life years, and cost effectiveness from a healthcare perspective. Analysis was by intention to treat. Results: No significant difference was found in time to first relapse (hazard ratio 0.87, 95% confidence interval 0.65 to 1.17, log rank P=0.28) or in the incidence of frequently relapsing nephrotic syndrome (extended course 60/114 (53%) v standard course 55/109 (50%), P=0.75), steroid dependent nephrotic syndrome (48/114 (42%) v 48/109 (44%), P=0.77), or requirement for alternative immunosuppressive treatment (62/114 (54%) v 61/109 (56%), P=0.81). Total prednisolone dose after completion of the trial drug was 6674 mg for the extended course versus 5475 mg for the standard course (P=0.07). There were no statistically significant differences in serious adverse event rates (extended course 19/114 (17%) v standard course 27/109 (25%), P=0.13) or adverse event rates, with the exception of behaviour, which was poorer in the standard course group. Scores on the Achenbach child behaviour checklist did not, however, differ. Extended course treatment was associated with a mean increase in generic quality of life (0.0162 additional quality adjusted life years, 95% confidence interval −0.005 to 0.037) and cost savings (difference −£1673 (2160; €1930), 95% confidence interval −£3455 to £109). Conclusions: Clinical outcomes did not improve when the initial course of prednisolone treatment was extended from eight to 16 weeks in UK children with steroid sensitive nephrotic syndrome. However, evidence was found of a short term health economic benefit through reduced resource use and increased quality of life. Trial registration: ISRCTN16645249 ; EudraCT 2010-022489-29.